"Teachers can arouse passion in their subject..." - pedagogical reflections in the memories of the Master - Renata Góralska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
The article presents the memories of Professor Józef Półturzycki - educationalist and academic teacher, long-term Professor at the University of Warsaw, the Nicolaus Copernicus University in Toruń and Pawel Wlodkowic University College in Płock. In his narration, Professor returns to the times of his childhood spent in Kresy ("Borderlands"), talks about his school years in Poznan and student days in Warsaw. He explains reasons of his interest in the theory of teaching, adult education, comparative literature and biography. From the narration, it is possible to learn about interesting and important moments referring both to Professor's scientific and private life.